Linking student behaviours and attitudes towards information and communication technology with learning processes, teacher instruction and classroom environment - Cavanagh, Rob; Romanoski, J. (Nova Science Publishers, Inc., 2011)
This chapter describes how the Rasch model was applied to construct an intervallevel scale measuring student use and disposition towards information and communication technology (ICT). Scale development was based upon an hypothesised model of classroom ICT learning culture comprising self and collective values, attitudes and behaviours. Specifically, the study aimed to produce a scale that: Measured student self-reported learning behaviours and attitudes towards use of ICT; had calibrated item difficulties and self-reported learning behaviours and attitudes towards ICT measures on the same scale; and elicited data to fit the theoretical model. A 126 item Likert scale type instrument was developed, administered to 439 primary and secondary school students, and then refined and validated by Rasch analysis. The validated data comprised 62 items on five aspects of ICT learning culture. These five aspects were: Student reported learning attitudes and behaviours; student reported teacher attitudes and behaviours; student reported attitudes and behaviours towards ICT networks; student reported home ICT attitudes and behaviours; and student reported values towards ICT use at school. Examination of the psychometric properties of the data identified common and uncommon attitudes and behaviours. This illustrated how students viewed their classroom ICT learning culture. © 2009 by Nova Science Publishers, Inc. All Rights Reserved.